Wiedza studentów na temat odnawialnych źródeł energii = Knowledge of students about renewable energy sources - Babula, Mateusz; Warchoł, Martyna (Journal of Education, Health and Sport, 2016)
Babula Mateusz, Warchoł Martyna. Wiedza studentów na temat odnawialnych źródeł energii = Knowledge of students about renewable energy sources. Journal of Education, Health and Sport. 2016;6(8):135-144. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59905 http://ojs.ukw.edu.pl/index.php/johs/article/view/3738 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Wiedza studentów na temat odnawialnych źródeł energii Knowledge of students about renewable energy sources Mateusz Babula1, Martyna Warchoł2 1Uniwersytet Technologiczno–Humanistyczny w Radomiu 2Uniwersytet Medyczny w Lublinie Słowa kluczowe: odnawialne źródła energii, energia odnawialna. Key words: renewable sources of energy, renewable energy. Streszczenie Wstęp: W dzisiejszych czasach do pracy wielu urządzeń potrzebna jest energia elektryczna. Obecnie około 90% energii elektrycznej powstaje w elektrowniach cieplnych, których paliwem jest węgiel kamienny lub brunatny. Poprzez produkcję energii elektrycznej w sposób konwencjonalny wzrasta zawartość w powietrzu dwutlenku węgla. Przyczynia się to do zwiększenia efektu cieplarnianego oraz do rosnącego zagrożenia związanego ze zmianami klimatycznymi. Dlatego ważne jest wykorzystanie odnawialnych źródeł energii. Cel pracy: Celem naszej pracy jest przedstawienie wiedzy studentów na temat OŹE. Badanie to ma na celu sprawdzenie znajomości definicji i podziału odnawialnych źródeł energii, korzyści oraz wad jakie wynikają z ich użytkowania oraz podstaw prawnych funkcjonowania OŹE w Polsce. Prowadzone badanie ma na celu przedstawienie wiedzy studentów na temat udziału OŹE w produkcji energii elektrycznej w Polsce. Materiał i metody badawcze: W badaniu zastosowano metodę sondażu diagnostycznego. Narzędziem badawczym był kwestionariusz ankiety własnego autorstwa złożony z 10 pytań. Dotyczą one wiedzy na temat Odnawialnych Źródeł Energii, znajomości definicji i podziału odnawialnych źródeł energii, korzyści oraz wad jakie wynikają z ich użytkowania oraz podstaw prawnych funkcjonowania OŹE w Polsce. Badania odbywały się na zasadzie anonimowości. Ankiety zostały wysyłane do respondentów za pomocą Internetu. Wyniki i wnioski: Większość studentów określa swoją wiedzę na temat Odnawialnych Źródeł Energii na poziomie dostatecznym. Zaś po przeprowadzeniu badań wykazano, że studenci potrafią zdefiniować pojęcie odnawialnych źródeł energii oraz poprawnie wymieniają jej źródła. Natomiast stwierdzono znaczne trudności w znajomości norm prawnych dotyczących tego tematu oraz wiedzy na temat ilości produkcji energii elektrycznej produkowanej z OŹE w kraju jak i na świecie. Studenci również mają kłopot z określeniem najobfitszych oraz najintensywniej wykorzystywanych źródeł energii odnawialnej. Nie znają również głównych źródeł energii odnawialnych wykorzystywanych w Polsce do produkcji energii cieplnej jak i elektrycznej. Abstract Introduction: Nowadays, the work of many devices need electricity. Currently, about 90% of the electricity produced in thermal power plants, where the fuel is coal or lignite. By producing electricity in a conventional manner in the air content increases carbon dioxide. This contributes to an increase in the greenhouse effect and to the growing threat of climate change. It is therefore important to use renewable energy sources. The aim of our work is to present the students' knowledge of RES. This study is designed to test knowledge of definitions and distribution of renewable energy sources, the benefits and disadvantages that result from their use and the legal basis for the operation of RES in Poland. Conducted study aims to present the students' knowledge on the share of RES in electricity production in Poland. Material and research methods: The study used diagnostic survey method. The research tool was a questionnaire by their own consisting of 10 questions. They concern the knowledge on Renewable Energy, the knowledge of the definition and distribution of renewable energy sources, the benefits and disadvantages that result from their use and the legal basis for the operation of RES in Poland. Research is carried out on an anonymous basis. Surveys were sent to respondents via the Internet. Results and conclusions: The majority of students determines their knowledge on Renewable Energy Sources at sufficient. And after study has shown that students are able to define the concept of renewable energy sources and correctly mention its source. In contrast, there were significant difficulties in the knowledge of the legal norms on the subject and knowledge of the amount of production of electricity from RES in the country and the world. Students also have trouble identifying most abundant and most extensively used renewable energy sources. They do not know the main sources of renewable energy used in Poland for the production of heat and electricity.